2016
DOI: 10.21511/im.12(2).2016.03
|View full text |Cite
|
Sign up to set email alerts
|

Determining consumers’ reasons for visiting shopping malls

Abstract: The level of competition in the retail market is high and demands a need to manage shopping malls appropriately and understand the general consumer behavior during visits at shopping mall in terms of their main reasons for visiting the mall and attitude in order to attract shopping mall visitors to visit these malls. The purpose of the study aimed to determine consumers' main reasons for visiting the shopping mall and their frequency of visits at the mall. A quantitative approach was followed to realize resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…Namun rata-rata penelitian pemodelan tarikan perjalanan pusat perbelanjaan hanya menekankan pada skala ukuran dan single use retail tanpa memperhatikan multi fungsi penggunaan aktivitas lainnya (Sasidhar dkk., 2016). Umumnya, suatu tempat yang dapat menampung banyak kegiatan di dalamnya (multi activity commercial centre) cenderung diminati oleh para pengunjung (Farrag, El Sayed, & Belk, 2010;Makgopa, 2016). Multi activity commercial memiliki karakteristik yang sama dengan mixed-use development yaitu adanya penggabungan beberapa jenis aktivitas dalam satu bangunan komersial.…”
Section: Pendahuluanunclassified
“…Namun rata-rata penelitian pemodelan tarikan perjalanan pusat perbelanjaan hanya menekankan pada skala ukuran dan single use retail tanpa memperhatikan multi fungsi penggunaan aktivitas lainnya (Sasidhar dkk., 2016). Umumnya, suatu tempat yang dapat menampung banyak kegiatan di dalamnya (multi activity commercial centre) cenderung diminati oleh para pengunjung (Farrag, El Sayed, & Belk, 2010;Makgopa, 2016). Multi activity commercial memiliki karakteristik yang sama dengan mixed-use development yaitu adanya penggabungan beberapa jenis aktivitas dalam satu bangunan komersial.…”
Section: Pendahuluanunclassified
“…Mall culture in Sri Lanka, particularly in urban areas, has developed significantly, with people drawn to the overall shopping mall experience and the convenience of the "one-stop shop" concept for a wide range of brands, products, and services. Shopping malls play a major role in building socialization for Gen Z, providing them with a place to spend quality time with their families and hang out with friends (Debsena, 2022;Makgopa, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It was indicated that utilizing the dimensions as a model would create an understanding for the development and analysis of behavior among consumers, reshape strategies, and develop the business to cater to consumers ( Chuenyindee et al, 2022 ). In addition, for further holistic measurement, the values of human behavior such as the utilitarian and hedonic values should be considered which affects consumer satisfaction ( Magkopa, 2016 ). Since the change in business strategy, pattern, and activity are in place due to the COVID-19 pandemic, reassessment of their current strategies should be explored.…”
Section: Introductionmentioning
confidence: 99%